2012
DOI: 10.1016/j.joen.2011.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain after Manual and Mechanical Glide Path: A Randomized Clinical Trial

Abstract: word count: 218 wordsText word count: 2555 words

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 28 publications
3
137
2
6
Order By: Relevance
“…Amongst the nonsteroidal anti-inflammatory drugs (NSAIDS), ibuprofen was selected because it is considered the standard medication for postoperative pain relief after root canal treatment (Parirokh et al 2014). In prospective randomized clinical trials, the maximum analgesic intake associated with postoperative pain was highly variable, with the prevalence ranging from 32% (Pasqualini et al 2012) to 75% (Ramamoorthi et al 2014). In the present study, the maximum analgesic intake reported was eight tablets (three of 55 patients) at all time intervals in the Vibringe group with no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the nonsteroidal anti-inflammatory drugs (NSAIDS), ibuprofen was selected because it is considered the standard medication for postoperative pain relief after root canal treatment (Parirokh et al 2014). In prospective randomized clinical trials, the maximum analgesic intake associated with postoperative pain was highly variable, with the prevalence ranging from 32% (Pasqualini et al 2012) to 75% (Ramamoorthi et al 2014). In the present study, the maximum analgesic intake reported was eight tablets (three of 55 patients) at all time intervals in the Vibringe group with no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators activate sensitive nociceptors and lead to central and peripheral hyperalgesia mechanisms. [1][2][3][4] In previous studies, the incidence of severe pain after treatment (flare-up) in retreatment cases has been reported to be significantly higher than for primary root canal treatment, emphasizing the need for a proper adapted method to prevent pain complication in retreatment cases. [5][6][7][8] To reduce the intensity of pain, the use of different modalities, such as intra canal therapy, analgesics or nonsteroidal anti-inflammatory drugs (NSAIDs) have been recommended.…”
Section: Introductionmentioning
confidence: 99%
“…However, these cases usually constitute a real emergency and frequently demand unscheduled visit for treatment [5]. Managing of postoperative pain has been the matter of many research studies, involving preoperative explanations and instructions [6], long-acting anesthesia [7], the glide path [8], occlusal reduction [9], treatment using salicylic acid [10], non-steroid anti-inflammatory drugs (NSAIDs) [11], combination of ibuprofen and acetaminophen [12], narcotic analgesics [13], a combination of narcotic analgesics with aspirin [14] or acetaminophen [15], and steroidal anti-inflammatory drugs [16].…”
mentioning
confidence: 99%